MRI findings of spring ligament injury: association with surgical findings and flatfoot deformity. (December 2020) - Kimura, Yusuke; Yamashiro, Tsuneo; Saito, Yuki; Kitsukawa, Kaoru; Niki, Hisateru; Mimura, Hidefumi
Background: Spring ligament injury is an important cause for flatfoot deformity; however, reliability of magnetic resonance imaging (MRI) findings of spring ligament injury is still ambiguous. Purpose: To investigate the reliability of MRI findings for the diagnosis of spring ligament injury. Material and methods: Forty-three cases with spring ligament injury proven by surgery and 29 control cases were enrolled. The spring ligament complex was demonstrated on proton density-weighted images reconstructed from 3D-isotropic MRI data. The presence of waviness, discontinuity, and abnormally high signal intensity of the spring ligament complex was evaluated by two radiologists in cooperation. Also, injury of the posterior tibial tendon (PTT) on MRI and the lateral talo-1st metatarsal angles on weight-bearing X-rays were evaluated. Results: Discontinuity and abnormally high signal intensity of the superomedial calcaneonavicular ligament (SmCNL) on MRI were more frequently observed in patients with spring ligament injury than in controls ( p < 0.001). Discontinuity and abnormally high signal intensity of the SmCNL were found more often in the PTT injury group than in those without ( p < 0.001). The talo-1st metatarsal angle was greater in patients with discontinuity and abnormally high signal intensity of the SmCNL on MRI than in patients without these findings ( p < 0.001). Conclusion: Discontinuity and abnormally high signal intensity are reliable MRI findings for spring ligament injury and related disorders, such as flatfoot deformity and PTT injury.